S. S. Zimnitsky — the creator of the functional direction in internal medicine. The outset — research in gastroenterology - V. N. Оslopov; E. V. Khazova; N. R. Khasanov; Yu. V. Oslopova; Yu. S. Mishanina; D. V. Oslopova (Кардиоваскулярная терапия и профилактика, 2023)
Semen Semenovich Zimnitsky is an outstanding Russian internist of the early XX century. He created a functional direction and made a significant contribution to internal medicine, infectiology, immunology and microbiology, but his studies of gastroenterology are fundamental. The Zimnitsky’s works on hepatology, pancreatic diseases, and balneology are interesting. S. S. Zimnitsky discovered 5 types of gastric secretion, which turned out to be reversible, and proposed a repeated breakfast. The pinnacle of his work is Zimnitsky’s test, which makes it possible to determine the renal function without resorting to any invasive procedures and in no way burdening the patient. The onset of test creation was laid by S. S. Zimnitsky in his doctoral dissertation devoted to gastroenterology.